Towards bridging the gap between Common Agriculture Policy implementation and pastures sustainable management: A case study from Tzoumerka, Greece - Roukos Ch.; Chatzitheodoridis F.; Kontogeorgos A. (Ecosystem services and socio-economic benefits of Mediterranean grasslands, 2016)
The CAP reform 2014 – 2020 maintains the two pillars and introduces a new architecture of direct payments; better targeted, more equitable and greener, an enhanced safety net and strengthened rural development. In order to highlight the gap between CAP implementation and pastures sustainable management, a case study was done in the area of Tzoumerka Mountain. The present paper, studies the national and European legal frame concerning pastures eligibility criteria for Pillar I payments, the current grasslands management and the main points of agricultural subsidies system relating with grassland management in Greece. The study points out the legal and technical complexity and the partial application of European regulations in pastures sustainable management. It seems that CAP is more an agriculture parcel-oriented policy rather than an intergraded policy sustainable pasture management. Finally, the adoption of a new policy bridging the gap between CAP implementation rules and pasture sustainable management is necessary.
15. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM International Network for the Research and Development of Pastures and Fodder Crops, 2016/04/12-14, Orestiada (Greece)